High prevalence of Babesia microti in small mammals in Beijing - Chun-Yan Wei; Xiao-Mei Wang; Zhen-Sheng Wang; Zhi-Hua Wang; Zeng-Zhi Guan; Lian-Hui Zhang; Xiang-Feng Dou; Heng Wang (BMC, 2020)
Abstract Background Babesiosis is an emerging tick-borne zoonotic infectious disease. Babesia microti is responsible for most cases of human babesiosis globally. It is important to investigate the prevalence of B. microti in the mammalian host population of a specific region in order to elucidate mechanisms of pathogen transmission and to define geographic areas where humans face the greatest risk of exposure. The aim of this study is to understand the prevalence and genotypes of B. microti in the small mammals that are found in Beijing, China. Methods We trapped small mammals from all of the 16 urban, suburban, and outer suburban districts of Beijing during the years 2014, 2017 and 2018. Genomic DNA was extracted from the heart tissues individually and the Babesia 18S rRNA gene was detected by PCR. The genotypes of B. microti were identified based on sequence alignments and phylogenetic analysis. The morphology of the parasites was observed under light microscopy. The risk factors were analyzed statistically based on both univariate analyses and multivariate logistic regression. Results A total of 1391 small mammals were collected. Positive infection of B. microti was detected in 12.1% (168/1391) of small mammals from 15 out of the 16 districts. Both Kobe-type and U.S.-type B. microti, accounting for 9.5% and 2.7%, respectively, were identified. Classic diverse morphologic forms of B. microti were observed. Specific types of ecological habitats including shrub areas, broad-leaved forest, and cropland were revealed to be risk factors associated with B. microti infection. Conclusions This study demonstrated the wide prevalence of B. microti infection in eight species of small mammals in Beijing, with Kobe-type more prevalent than U.S.-type. This study provides fundamental information for the development of informed prevention and control measures by public health authorities; the data gathered indicates a need for further monitoring of both clinical diseases in individuals presenting with babesiosis-like symptoms, as well as the infection status of ticks in high risk areas.